The influence of emotional intelligence in the workplace environment: A literature review - Johennesse, Lee-Anne; Pressley, Gareth (Indonesian Journal of Business, Accounting and Management, 2023)
This study examines the influence of emotional intelligence in the working environment that will affect both employee and company performance. This area of study involves people, the environment in which they live and work, how they affect their environment, and the effect that environment has upon them. Emotional intelligence is tied to adaptation, which is the process by which a person adjusts to external conditions to diminish disruption and maximize benefits. It is a favorable human trait associated with several beneficial life outcomes. Many research models are utilized to measure and capture the ability to conceptualize emotional intelligence as potential performance, and they use performance-based measures of emotional intelligence to achieve good performance. The aim of this research is to reflect the comprehensive studies within this realm regarding the utility of emotional intelligence in an organizational context. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.